The dark side of the rainbow: queer women’s experiences of intimate partner violence - Harden, Jacqueline L. (Kansas State University, 2020)
Intimate Partner Violence (IPV) is a worldwide issue that, although often thought of as a very gendered and heteronormative crime (male perpetrators and female victims within heterosexual relationships), occurs in all kinds of relationships. The purpose of this study is to examine and raise awareness of how IPV operates within female same-gender relationships. Researchers utilized a narrative inquiry framework, as well as thematic analysis, in order to conduct a qualitative synthesis of articles that examined IPV in female same-gender relationships. Articles were identified through database searches for studies published between 2000 and 2019 using key search terms. Studies were included if they were qualitative in nature (including direct quotes from participants), examined IPV within female same-gender relationships, and were written in English. A total of 19 studies were included in the qualitative synthesis. Findings were categorized as either barriers to help and support, themes within experiences of IPV, or recommendations for helping professionals. Themes within categories included, among others: a lack of framework to identify abuse, mistrust of law enforcement, power dynamics related to parenthood, race, and gender presentation, and fears of contributing to heterosexism. Findings from this study can serve to better inform helping professionals about considerations to keep in mind when working within LGBT+ communities, as well as survivors of female same-gender violence.
Keywords: intimate partner violence; LGBT+